The effect of suspended sentences on imprisonment - Don Weatherburn
This study finds that although suspended sentences were introduced as an alternative to prison, in New South Wales they appear to have had the opposite effect. Abstract Aim: To see whether the introduction of suspended sentences reduced the number of offenders receiving a fulltime sentence of imprisonment. Method: The number of persons receiving a prison sentence was regressed against the number receiving a suspended sentence while controlling for changes in the total number of proven offenders and the monthly variability using multiple linear regression with ARIMA errors. The data set used for the analysis consisted of the monthly number of persons imprisoned, persons given a suspended sentence and proven offenders from January 2002 to December 2013. Results: Every 10 additional offenders given suspended sentences was associated with an extra 3-4 offenders sent to prison. Conclusion: Although suspended sentences were introduced as an alternative to prison, they appear to have had the opposite effect